Tell Me about Your Research and I will Tell You Who You Are. About the Interlocking of Personal Life with the Scientific Work in the Context of Auto/Biographical Research Practices - Pryszmont-Ciesielska, Martyna (INSTED: Interdisciplinary Studies in Education & Society, 2017)
The writer draws a reflection about the cognitive and methodological value of auto/biographical practices, focused on seeking the links between a scientific and professional biography. The essence of those approaches is the inclusion of researcher?s personal experiences in the course of the research process. Thereby, that perspective becomes an important source of (re)cognising social worlds. The natural context of the conducted research makes auto/biography entangled with auto-etnography, because each research always has a territory which is explored and experienced by the researcher. On the other hand, each ?novel? that comes from the research sphere will have subjective marks of the researcher who is present there. Therefore, each research has its own trajectory, where the researcher?s ?self? is inscribed. The presence of the reflection over their own ?self? gives the researcher not only the possibility of showing their own personal experiences, but also taking on a critical reflection over a role which is played by them in the conducted research. The point is to seek relations between the interpretation perspective and the autobiography of the cognition subject.